Strategic Placement of In-line Turbines for Optimum Power Generation and Leakage Reduction in Water Supply Networks - Jain, Priyanshu; Khare, Ruchi (Water resources management, 2024)
Conduit hydropower systems improve the efficiency of water supply networks (WSNs) by utilizing excess network pressure for providing renewable energy while significantly reducing leakage. A major problem in using conduit hydropower is finding the optimum location for installing power generation devices like in-line turbines or pumps operating as turbines (PATs). This paper suggests an optimization model to find the optimum location for placing in-line turbines in WSNs using a non-parametric Rao algorithm for optimal daily power generation. The methodology is tested on a hypothetical 5-Node network and later applied to a benchmark 25-Node network. Installing turbines at optimum locations reduced network leakage by 76332.00 and 380473.87 L, representing approximately 2.57% & 2.94% of the total water demand of 5-Node and 25-Node networks, respectively, and generated 184.12 & 547.48 kWh/day of hydropower.